New directions in the history of the Jews in the Polish lands - Polonsky, Antony; Węgrzynek, Hanna; Żbikowski, Andrzej (Jews of Poland., 2018)
"This volume is made up of essays in first presented as papers at the conference held in May 2015 at the POLIN museum of the history of Polish Jews in Warsaw is divided into two sections. The first deals with museological questions--the voices of the curators, comments on the museum and discussions of museums and education. The second examines the current state of the historiography of the Jews on the Polish lands from the first Jewish settlement to the present-day. Making use of the leading scholars in the field from Poland, Western Europe, North America and Israel, the volume provides a definitive overview of the history and culture of one of the most important communities in the long history of the Jewish people"--